(untitled) (Eurasian Journal of Media and Communications, 2021)
In order to develop the activities of free economic zones and logistics centers in Uzbekistan, to address the problems in this process, the index of logistics indicators of developed countries, the analysis of the experience of supporting logistics centers are presented